Die Gemeinschaftlichkeit der Beweismittel Ein Beitrag zur Lehre von den prozessualen Mitwirkungspflichten - Riss, Olaf (Jan Sramek Verlag, 2016)
In the part regarding taking of evidence of the Austrian Code of Civil Procedure, one can find provisions referring to so called common pieces of evidence. In academic literature a general principle of right to provide evidence is derived therefrom according to which a party in a lawsuit is obliged to assist and support also the opposing party to a certain extent. One of the facts by which such duty to cooperate is imposed on the parties by procedural law are common pieces of evidence.